4-[(E)-(5-tert-Butyl-2-hydroxyphenyl)-diazenyl]benzoic acid benzene hemisolvate - Baul, T.S.B.; Paul, A.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The title benzene hemisolvate, C17H18N2O3 center dot 0.5C(6)H(6), features an essentially planar (the r.m.s. deviation of the non-H atoms, excluding methyl-C, is 0.071 angstrom) diazo molecule with an E conformation about the N=N bond, and a half-molecule of benzene disposed about a centre of inversion. The dihedral angle formed between the benzene rings of the diazo molecule is 7.69 (12)degrees. In the crystal, centrosymmetrically related dimers associate via the eight-membered carboxylic acid dimer synthon, {center dot center dot center dot HOC(=O)}(2), and these are connected into a supramolecular chain along the b axis via C-H center dot center dot center dot O contacts.